Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kinerja Karyawan PT. Putra Perdana Indoniaga - Endang Triwidyati; Desi Kristanti; Nonni Nonni (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Employee performance is one of the factors that affect the level of success of an organization. This is because employees as human resources are the movers and determinants of the running of an organization or company. Factors that affect employee performance are work environment and work stress. This study aims to determine the effect of work environment and work stress on employee performance at PT. Putra Perdana Indoniaga (Wuling Motor Cab. Jombang. The population of this study was 25 employees and the sample taken was a saturated sample, that is, the entire population was used as the research sample. The data collection method in this study used a questionnaire with a scale of 1 to 5. The collected data will be analyzed with multiple linear regression technique. The results show that the work environment (X1) has a tcount value of 3,227 which is greater than the ttable value at a significant level of Â± "2,074" with a significance number below 0.05 which means there is a significant influence between the work environment The work stress variable (X2) has a Coefficient t of -2.387 which is greater than the ttable value for the real level of Â± "2.074" and has a significant value below 0.05 so that work stress (X1) has an effect on the dependent variable. Performance Employees (Y). While simultaneously or together, value of Fcount of 10.809 > Ftable 0.715 which means that at the level of significance = 0.05, the variables of Work Environment (X1) and Work Stress (X2) simultaneously have a significant (meaningful) effect on Employee Performance (Y). Keywords : Work Environment, Work Stress, Employee Performance